Upaya Peningkatan Kinerja bagian Sekretariat Berbasis Lingkungan Kerja Fisik dan Motivasi Kerja pada Kantor Dinas X - Fung, Tham Lie; Rachmat Mulyana, Aam (Journal of Management and Bussines (JOMB), 2024)
This study aims to analyze the influence of physical work environment and work motivation on the performance of secretariat employees, both partially and simultaneously. The research method used is a quantitative approach, with data collection techniques through library and field research, including interviews, questionnaires, and documentation. Data were analyzed using multiple linear regression with the help of SPSS. Respondents in this study amounted to 68 employees. The results of the study indicate that the physical work environment does not have a significant effect on employee performance, while work motivation has a positive effect. Simultaneously, the physical work environment and work motivation affect employee performance. In conclusion, high work motivation is related to better employee performance. In addition, the response to the physical work environment in the Office of Service X is in the sufficient criteria with the highest security sub-variable and the lowest lighting, while work motivation is considered good with success as the highest variable and potential for self-development as the lowest. The performance of the State Civil Apparatus (ASN) is considered good with an emphasis on costs as the highest sub-variable and relationships between employees as the lowest. Overall, the influence of the physical work environment and work motivation on the performance of ASN in the Office of Service X shows a significant influence. Keywords: Physical Work Environment, Performance, Work Motivation